2020
DOI: 10.1080/02670844.2019.1701858
|View full text |Cite
|
Sign up to set email alerts
|

Influence of carbide particle size on the wear performance of cryogenically treated H13 die steel

Abstract: Cryogenic treatment could be useful in preventing AISI H13 steel forging dies from the premature failure that is continuously under the action of mechanical stresses and temperature. This work involves heating H13 steel specimens to 1020°C, quenching in oil followed by double tempering at 520°C for 2 h subsequently undergoing cryogenic treatment at minus185°C for cryosoaking periods starting from 8 to 32 h. Dry sliding wear tests were performed at room temperature on pin-on-disc wear testing machine at 40 N lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…Between the cryogenic temperature and holding time, the cryogenic temperature is the most influencing parameter, followed by holding time as the second influencing parameter, which agrees with the findings of Darwin et al [40]. Many researchers have found that lowering cryogenic temperature could obtain more improvement in wear resistance of steels, and the optimum value of cryogenic temperature was −196°C [9,25,41,42]. Similarly but slightly different in this work, cryogenic treatment at −160°C obtained more improvement of wear resistance than −120°C, and wear resistance at −196°C improved almost the same as −160°C, only higher by 0.29%, which may be due to the introduction of multiple cycles of cryogenic treatment.…”
Section: Discussionsupporting
confidence: 84%
“…Between the cryogenic temperature and holding time, the cryogenic temperature is the most influencing parameter, followed by holding time as the second influencing parameter, which agrees with the findings of Darwin et al [40]. Many researchers have found that lowering cryogenic temperature could obtain more improvement in wear resistance of steels, and the optimum value of cryogenic temperature was −196°C [9,25,41,42]. Similarly but slightly different in this work, cryogenic treatment at −160°C obtained more improvement of wear resistance than −120°C, and wear resistance at −196°C improved almost the same as −160°C, only higher by 0.29%, which may be due to the introduction of multiple cycles of cryogenic treatment.…”
Section: Discussionsupporting
confidence: 84%
“…Cryogenic and tempering treatment can promote the transformation of retained austenite and precipitate stable carbonitrides, resulting in a significant strengthening effect. [ 29–31 ] In addition, the severe quenching stress caused by martensitic transformation and high alloy elements contents can be also eliminated or reduced by tempering treatment. [ 32 ] The detailed processes are shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…It was stated that minimum wear rate occurs at minimum carbide particles size. 115 Mani in his research on turning of Inconel 625 observed that cryogenic treatment helped in increasing tool life by lowering the heat generation which helped in reducing tool wear. The results of cryogenic turning showed improvement of surface roughness which was found to be 50.52% as compared to dry turning.…”
Section: Wear Resistancementioning
confidence: 99%